Kitlo hematopoietic stem cells exhibit distinct lymphoid-primed chromatin landscapes that enhance thymic reconstitution - Harold K. Elias; Sneha Mitra; Marina B. da Silva; Adhithi Rajagopalan; Brianna Gipson; Nicole Lee; Anastasia I. Kousa; Mohamed A. E. Ali; Simon Grassmann; Rhoshini Raghuraman; Xiaoqun C. Zhang; Susan DeWolf; et al. (Nature Communications)
Abstract Hematopoietic stem cells (HSC) with multilineage potential are critical for T cell reconstitution after allogeneic hematopoietic cell transplantation (allo-HCT). The Kitlo HSC subset is enriched for multipotential precursors, but their T cell potential remains poorly characterized. Using a preclinical allo-HCT mouse model, we demonstrate that Kitlo HSCs provide superior thymic recovery and T cell reconstitution, resulting in improved immune responses to post-transplant infection. Kitlo HSCs with augmented bone marrow (BM) lymphopoiesis mitigate age-associated thymic alterations and enhance T cell recovery in middle-aged mice. Mechanistically, chromatin profiling reveals Kitlo HSCs exhibiting higher activity of lymphoid-specifying transcription factors, such as, ZBTB1. Zbtb1 deletion diminishes HSC engraftment and T cell potential; by contrast, reinstating Zbtb1 in megakaryocytic-biased Kithi HSCs rescues hematopoietic engraftment and T cell potential in vitro and in vivo. Furthermore, age-associated decline in Kitlo HSCs is associated with diminished T lymphopoietic potential in aged BM precursors; meanwhile, Kitlo HSCs in aged mice maintain enhanced lymphoid potential, but their per-cell capacity is diminished. Lastly, we observe an analogous human BM KITlo HSC subset with enhanced lymphoid potential. Our results thus uncover an age-related epigenetic regulation of lymphoid-competent Kitlo HSCs for T cell reconstitution.